Forest stand structure, productivity, and age mediate climatic effects on aspen decline. Issue 8 (1st August 2014) - Bell, David M.; Bradford, John B.; Lauenroth, William K.
Abstract : Because forest stand structure, age, and productivity can mediate the impacts of climate on quaking aspen ( Populus tremuloides ) mortality, ignoring stand‐scale factors limits inference on the drivers of recent sudden aspen decline. Using the proportion of aspen trees that were dead as an index of recent mortality at 841 forest inventory plots, we examined the relationship of this mortality index to forest structure and climate in the Rocky Mountains and Intermountain Western United States. We found that forest structure explained most of the patterns in mortality indices, but that variation in growing‐season vapor pressure deficit and winter precipitation over the last 20 years was important. Mortality index sensitivity to precipitation was highest in forests where aspen exhibited high densities, relative basal areas, quadratic mean diameters, and productivities, whereas sensitivity to vapor pressure deficit was highest in young forest stands. These results indicate that the effects of drought on mortality may be mediated by forest stand development, competition with encroaching conifers, and physiological vulnerabilities of large trees to drought. By examining mortality index responses to both forest structure and climate, we show that forest succession cannot be ignored in studies attempting to understand the causes and consequences of sudden aspen decline.